[Public smoking resource inventory] (Tufts Archival Research Center, 2007)
Resource Inventory for the Tobacco Institute's public smoking project. Contains a list of potential witnesses and their field of expertise. Lists additional resources available such as studies and publications supporting the TI's stance on public smoking.